2018
DOI: 10.1002/lno.10943
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of ancient organic carbon by zooplankton in Tibetan Plateau lakes is depending on watershed characteristics

Abstract: Ancient (i.e., radiocarbon depleted) organic carbon (OC) is exported from ice sheet, glacier, and permafrost systems and may be buried, respired, or assimilated in downstream aquatic systems. Few studies have explored the potential use of this ancient OC in lake food webs. We combined natural abundance radiocarbon and stable carbon isotope data (Δ14C and δ13C) to study ancient OC utilization by zooplankton in six lakes covering a large climate gradient on the central and peripheral Tibetan Plateau. A depleted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Daphnia magna had a more depleted ∆ 14 C value than its carbon sources in most groups with the exception of group CB. This probably reflects how terrestrial OC may be recycled by the respiration or other metabolic processes of organisms, such as algae and zooplankton (Rau, 1978; Su et al., 2018). Interestingly, the Δ 14 C value of D. magna in group CB was more enriched than in CA and closer to that of Auxenochlorella than degraded ancient DOC, probably reflecting that D. magna in CB assimilated more Δ 14 C‐enriched Auxenochlorella than those in CA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daphnia magna had a more depleted ∆ 14 C value than its carbon sources in most groups with the exception of group CB. This probably reflects how terrestrial OC may be recycled by the respiration or other metabolic processes of organisms, such as algae and zooplankton (Rau, 1978; Su et al., 2018). Interestingly, the Δ 14 C value of D. magna in group CB was more enriched than in CA and closer to that of Auxenochlorella than degraded ancient DOC, probably reflecting that D. magna in CB assimilated more Δ 14 C‐enriched Auxenochlorella than those in CA.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, D. magna had a depleted ∆ 14 C value, which was caused by both Auxenochlorella and ancient DOC. A previous field study had reported that zooplankton can obtain 14 C‐depleted signatures from allochthonous ancient dissolved and particulate OC, and autochthonous phytoplankton utilising 14 C‐depleted inorganic carbon (Su et al., 2018). In this study, Auxenochlorella showed a depleted Δ 14 C value (−161.6‰).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation